hmwk1 - Johny Nguyen September 16th, 2009 CS 473 Homework 1...

Info iconThis preview shows pages 1–7. Sign up to view the full content.

View Full Document Right Arrow Icon
Johny Nguyen September 16 th , 2009 CS 473 Homework 1 Downey
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
PROBLEM 1 Draw directed graphs representing relations of the following types: (a) Reflexive, transitive and antisymmetric . Antisymmetry of R means that ( 2200 a , b ) if ( a , b ) R and a b, then ( b , a ) R . (b) Reflexive, transitive, and neither symmetric nor antisymmetric.
Background image of page 2
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
PROBLEM 2 What is the reflexive, transitive closure R * of R = {( a , b ) ,( a , d ) ,( d , c ) ,( d , e )}? Express R * as a set, and also draw a directed graph representing the relation R *. R* = {(a,a), (b,b), (c,c), (d,d), (e,e), (a,e), (a,c), (a,b), (a,d), (d,c), (d,e)}
Background image of page 4
PROBLEM 3 i. A ( n , 0) = n + 1 ii. A (0, m + 1) = A (1, m ) iii. A ( n + 1, m + 1) = A ( A ( n , m + 1) , m ) A(n,m) = A ( A ( n - 1, m ) , m - 1) (a) A(n,1) = A( A(n-1, 1), 0) A(n,1) = A(n-1, 1) + 1 by (i) A(n-1, 1) = A(n-2,1) + 1 A(n,1) = A(n-2,1) + 2 A(n,1) = A(n-k,1) + k, Let k = n A(n-1) = A(0,1) + n A(n,1) = A(1,0) + n by (ii) A(n,1) = 2 + n
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Proof: Base: n = 1. A(1,1) = 2 + 1 = 3 A(1,1) = A(1-1,1) + 1 = A(0,1) + 1 = A(1,0) + 1 = 2 + 1 = 3 Inductive: Suppose A(k, 1) = k + 2, then A(k+1,1) = (k + 1) + 2 = k + 3. A(k+1,1) = A((k+1)-1,1) + 1 = A(k,1) + 1 A(k+1,1) = A(k,1) + 1 = (k+2) + 1, By Inductive Hypothesis A(k+1,1) = k + 3. QED (b) A(n,2) = A( A(n-1, 2), 1) A(n,2) = A(n-1,2) + 2 by (a) A(n-1,2) + 2 = A(n-2,2) + 2 A(n,2) = (A(n-2,2) + 2) + 2 = A(n-2,2) + 2*2 A(n-2,2) = A(n-3,2) + 2 A(n,2) = (A(n-3,2) + 2) + 2*2 = A(n-3,2) + 3*2 A(n,2) = A(n-k,2) + 2k, Let k = n A(n,2) = A(0,2) + 2n A(n,2) = A(1,1) + 2n by (ii) A(n,2) = 3 + 2n by (a) Proof: Base: n = 1. A(1,2) = 3 + (2*1) = 3 + 2 = 5
Background image of page 6
Image of page 7
This is the end of the preview. Sign up to access the rest of the document.

Page1 / 12

hmwk1 - Johny Nguyen September 16th, 2009 CS 473 Homework 1...

This preview shows document pages 1 - 7. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online